Challenges to Diabetes Self-Management in Emerging Adults With Type 1 Diabetes. Issue 5 (October 2019) - Ramchandani, Neesha; Way, Niobe; Melkus, Gail D'Eramo; Sullivan-Bolyai, Susan
Purpose: The purpose of this qualitative descriptive study undergirded by Meleis's Transition Framework was to explore developmental, situational, and organizational challenges experienced by a diverse group of emerging adults (18-29 years old) with type 1 diabetes (T1DM). Their perspectives on creating a developmentally informed diabetes self-management (DSM) program that supports transitional care were also explored. Methods: A purposive sample of emerging adults with T1DM was recruited from the pediatric and adult diabetes clinics of an urban academic medical center. Those who consented participated in either a single focus group or a single interview. Self-reported demographic and clinical information was also collected. Results: The sample was comprised of 21 emerging adults, with an average age of 23.6 ± 2.6 years, diabetes duration of 14.7 ± 5.0 years, and 71% female. Four main themes emerged: (1) finding a balance between diabetes and life, (2) the desire to be in control of their diabetes, (3) the hidden burden of diabetes, and (4) the desire to have a connection with their diabetes provider. Use of insulin pumps and continuous glucose monitors and attendance at diabetes camp decreased some of the DSM challenges. Different groups of individuals had different perspectives on living with diabetes and different approaches to DSM. Conclusions: The emerging adults in this study had a strong desire to be in good glycemic control. However, all participants described having a hard time balancing DSM with other competing life priorities. They also desired personalized patient-provider interactions with their diabetes care provider in clinical follow-up services. Even though the study sample was small, important themes emerged that warrant further exploration.